Nutritional Evaluation of Sheabutter Fat in Fattening of Yankasa Sheep - Yusuf, A.M.; Olafadehan, O.A.; Obun, C.O.; Inuwa, M.; Garba, M.H.; Shagwa, S.M. (Pakistan Journal of Nutrition, 2009)
Fifteen Yankasa rams, balanced for their weight, were used to evaluate the effects of feeding basal diet of Pterocarpus erinaceus forage supplemented with Sheabutter Fat (SBF) based concentrate diets on performance, nutrient digestibility and economic benefit. The rams were submitted to four supplemental diets containing: 0 g/kg SBF (control), 50 g/kg SBF and 100 g/kg SBF in a completely randomized design for 56 days. Average Daily Gain (ADG), intakes of Ether Extract (EE) and Crude Protein (CP), Feed Conversion Ratio (FCR), digestibility coefficients of EE and Organic Matter (OM), digestible OM, digestible and metabolizable energy concentrations and net benefit improved (p